Modelling heterotypic cell interactions in the context of Barrett’s Oesophagus progression - Ruiz Puig, C (2020)
Oesophageal adenocarcinoma originates in the gastroesophageal junction and has a poor prognosis. Barrett’s oesophagus is a common, innocuous condition occurring prior to most adenocarcinoma cases. This lesion is frequent in patients suffering from gastroduodenal reflux and involves columnar cells replacing a segment of the squamous lining of the distal oesophagus. High variability in the length of the segment exists between individuals and typically patients with longer lesions have an increased risk of developing adenocarcinoma. However, the pathways promoting this replacement and determining its final length are unknown. In this thesis, I investigate models to study this phenomenon in vitro.